A comparison of visual and semiquantitative analysis methods for planar cardiac 123I-MIBG scintigraphy in dementia with Lewy bodies. Issue 7 (July 2019) - Roberts, Gemma; Kane, Joseph P.M.; Lloyd, Jim J.; Petrides, George S.; Howe, Kim; O'Brien, John T.; Thomas, Alan J.
Abstract : Objectives: Cardiac 123 I-MIBG imaging is an established technique for the diagnosis of dementia with Lewy bodies but various analysis methods are reported in the literature. We assessed different methods in the same cohort of patients to inform best practice. Patients and methods: Seventeen patients with dementia with Lewy bodies, 15 with Alzheimer's disease and 16 controls were included. Planar images were acquired 20 min and 4 h after injection. Nine operators produced heart-to-mediastinum ratios (HMRs) using freehand and 6, 7 and 8 cm diameter circular cardiac regions. Interoperator variation was measured using the coefficient of variation. HMR differences between methods were assessed using analysis of variance. Seven raters assessed the images visually. Accuracy was compared using receiver operating characteristic analysis. Results: There were significant differences in HMR between region methods ( P =0.006). However, with optimised cut-offs there was no significant difference in accuracy ( P =0.2–1.0). The sensitivity was 65–71% and specificity 100% for all HMR methods. Variation was lower with fixed regions than freehand ( P <0.001). Visual rating sensitivity and specificity were 65 and 77% on early images and 76 and 71% on delayed images. There was no significant difference in HMR between early and delayed images ( P =0.4–0.7) although a greater separation between means was seen on delayed images (0.73 vs. 0.95). Conclusion: HMR analysis using a suitable cut-off is more accurate than visual rating. Accuracy is similar for all methods, but freehand regions are more variable and 6 cm circles easiest to place. We recommend calculating HMR using a 6 cm circular cardiac region of interest on delayed images.